IMPLEMENTATION OF ANIMAL WELFARE IN BALI CATTLE FARMS IN SEBATU AND TARO VILLAGE, GIANYAR, BALI - Dina Elviana; Kadek Karang Agustina; I Ketut Suada; I Made Sukada (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Demand for beef continues to increase, this creates an opportunity for Bali cattle breeders to increase their production. The decline in cattle production can also be influenced by a lack of public knowledge about livestock management and a lack of knowledge and implementation of animal welfare. The aim of the research is to determine the implementation of animal welfare on Balinese cattle farms in Sebatu Village and Taro Village, Tegallalang District, Gianyar Regency. This research uses an observational method by interviewing cattle breeders directly. The number of respondents was 40 families who were raising cattle in Sebatu Village and Taro Village, Tegallalang District, Gianyar Regency, Bali. The research results show that the implementation of animal welfare in Sebatu Village is in the good category as much as 50% and 50% is very good, while in Taro Village the implementation of animal welfare in the good category is 65% and very good 35%. It can be concluded that the application of animal welfare principles in the two sample villages does not show significant differences. It is recommended to carry out further research regarding the fulfillment of minimum animal welfare standards on Balinese cattle farms throughout Bali